2021
DOI: 10.3390/en14164980
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels for Maritime Transportation: A Spatial, Techno-Economic, and Logistic Analysis in Brazil, Europe, South Africa, and the USA

Abstract: Low or zero carbon fuels are crucial for maritime transportation decarbonization goals. This paper assesses potential localities for maritime biofuels (biobunkers) production in Brazil, Europe, South Africa, and United States considering geographical, logistic, and economic aspects. This assessment combines georeferenced and techno-economic analyses to identify suitable fuel production hotspots based on not only plant performance and costs but also on logistic integration and biomass seasonality. Five technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Finally, in the deep decarbonization scenario (Brazil compatible with a world well below 2°C), the need for CCS engendered a significant synergy between shipping and road transport (and, on a much smaller scale, between aviation and shipping). In short, for all cases, the total annual potential exceeds by far the current demand of both sectors ( Carvalho et al., 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, in the deep decarbonization scenario (Brazil compatible with a world well below 2°C), the need for CCS engendered a significant synergy between shipping and road transport (and, on a much smaller scale, between aviation and shipping). In short, for all cases, the total annual potential exceeds by far the current demand of both sectors ( Carvalho et al., 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…(2018) IAMC (2020) de Oliveira et al. (2021) ( Müller-Casseres et al, 2021a ) Other Fischer-Tropsch BtL plant costs Historical aviation demand Historical marine fuel demand Historical foreign trade International trade scenarios ( Carvalho et al, 2021b ) ANAC (2021) EPE ( 2019b) ( MDIC, 2020 ) IMO (2015) and DNV GL (2018) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the maritime sector, Carvalho et al [38] suggested establishing mandatory fuel blends and joining forces with other sectors that would be benefited from the co-production of advanced biofuels.…”
Section: Biofuelsmentioning
confidence: 99%